RME model based on ethnomathematics “prol tape” typical of Jember in improving fraction concept understanding of madrasah ibtidaiyah students - Sufraini, Sufraini; Dewanti, Sintha Sih; Anriani, Titi; Budi, Tegar Setia; Isnaini, Safira Wahyu (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: This research stems from the problem of learning mathematics, which is still considered scary and difficult. Less varied learning methods make this learning boring for students. Through the development of this Realistic Mathematics Education (RME) learning model based on Jember's typical prol tape ethnomathematics, students enjoy learning more.Aim: This research aims to develop an RME learning model based on ethnomathematics "prol tape" typical of Jember City in improving the understanding of the concept of fractions of Madrasah Ibtidaiyah (MI) students.Method: This research is a kind of R&D (Research and Development) development research, using the 4-D development model (four D models) developed by Thiagarajan. This research was conducted at MI Ar-Roudhoh in the even semester of the academic year 2023/2024, with the research subjects being grade 2 teachers and grade 2 students. Data collection techniques through interviews, observations, and documentation.Result: The results showed that the percentage of students' learning completeness, namely 86.36%, met the criteria so that the developed products were effective for use. The obtained average N-gain value of 0.77 is in the high category, indicating that the application of the ethnomathematics based RME learning model can improve students' concept understanding ability on fraction material. Students' responses also showed a positive response, besides knowing the story, this media can make it easier for them to learn fraction material.Conclusion: This research can provide insight into how an RME learning model can be developed by integrating mathematics with local culture. The conclusions drawn here contribute to a broader understanding of the RME learning model in mathematics learning, providing a new perspective by innovating learning strategies used in educational practice.